2022
DOI: 10.1186/s13063-022-07013-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging the time of progesterone supplementation to improve the pregnancy outcomes of single day 6 blastocyst transfer in frozen-thawed cycles: study protocol for a randomized controlled trial

Abstract: Background Infertility is one of the most important and underappreciated reproductive health problems in developing countries. Currently, in vitro fertilization and embryo transfer is the most effective treatment strategy for infertility. In a frozen-thawed cycle, single-blastocyst transfer can not only ensure relatively higher pregnancy and live birth rates but also effectively reduce the risk of maternal and neonatal complications. In frozen-thawed cycles, progesterone is initiated to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Thus, delaying the day of embryo transfer is feasible (36, 37). Perhaps, the extended day is also theoretically covered by the implantation window (29). This viewpoint seems to have been recognized in the present study.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Thus, delaying the day of embryo transfer is feasible (36, 37). Perhaps, the extended day is also theoretically covered by the implantation window (29). This viewpoint seems to have been recognized in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…However, there are always some unavoidable factors that lead to the incomplete synchronous development of the embryos and endometrium (27,28). Although some previous studies have indicated that appropriately delaying the transfer time may improve the outcomes of FET (29), another data did not show any difference in clinical pregnancy rates between protocols with or without prolonged progesterone supplementation before FET (30).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations